Strategy of the School Principal in Increasing the Quality of Humanistic Perspective Human Resources Management - Helmi, Sulaiman; Setyadi, Bakti; Aryasari, Devita (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
This study examines school principals' strategies to improve human resource management quality based on a humanistic perspective. This research uses descriptive qualitative. This study uses the systematic literature review method to describe facts, data, and information obtained from literature studies, books, and journals on research results related to research topics. The study results show that school principals have a vital role in managing and improving the quality of the human resources they care for. The humanistic perspective is an individual study with its uniqueness and peculiarities, forcing the principal to formulate various strategic steps to implement it. Some efforts that can be made from this perspective based on the literature review conducted are establishing good cooperative relationships with all components in the school environment, building commitment and improving the quality of communication, and providing the best examples so that they can become a source of motivation to enhance self-quality.